Multimedia Discourse as an Element of Multiculture - Kholod, Oleksandr (East European Journal of Psycholinguistics, 2014)
Today it is not enough to determine the degree of the media influence, as we need to find an answer to the question of  how multimedia discourse as an element of multiculture in multisociety (“new electronic culture” –  M. Castells’s term) is associated with transformation (change) of consciousness of society. It is necessary to analyze inmutational and mutational (O. Kholod’s terms) changes in the minds of individuals, who, probably, make unintentional “quiet change” of thought creating and thus – the structure of world order. There are other issues:  whether to consider the current TV mass media provocative, and pushing society to negative behavior scenarios. Does television spoil public consciousness, or make negative (inmutational) changes in behavior, encouraging inmutational transformation of consciousness? In search of answers to those questions, the study has been carried out, which aimed at finding out the correlation of “new electronic culture” and “the transformation of consciousness” factors.ReferencesAlekseeva, A. Castells: nasha zizn – i hybrid vyrtualnoho fyzycheskoho v mire [Electronicresource]. Retrieved 1.10.2013 from: http: //ria.ru/interview/20120622/679289114.htm.Winnick, D. Google there – not upon the mind? [Electronic resource]. Retrieved 1.10.2013 from:http: //therunet.com/articles/1507-google-est-uma-ne-nado.Carr, N. Google delaet nus glupee? [Electronic resource]. Retrieved 1.10.2013 from: http://media-ecology.blogspot.com/2011/03/google.html.Castells, M. Informatsyonnaya era [Electronic resource]. Retrieved 1.10.2013 from: http://www.mashka-inc.narod.ru/books/castels.htmlConvergence telekommunication systems [Electronic resource]. Retrieved 1.10.2013 from: http://ru.wikipedia.org/wiki/Конвергенция_(Telecommunications).Puschaev, V. Liberalism, kvazylyberalnyj myfy i media svoboda (Karl Popper pro rolltelevydenyya v obschestve) [Electronic resource] Retrieved 1.10.2013 from: http: //progsshool.ru/voprosy-filosofii/page,2,723-liberalizm-kvaziliberalnye-mify-i-svoboda-smi.htmlKholod, O. (2011). Theoryja inmutatsiyi obschestva. Kyiv: KIMU.Kholod, O. (2013). Hypermarket svidomosty i mass media: Transformatsija svidomosti[Hypermarket of Mind and Mass Media: Transformation of Mind]. Kyiv: KNUKiM.Carr, N. (2008). Is Google Making Us Stupid? What the Internet is doing to our brains[Electronic resource]. Retrieved 1.10.2013 from: http: //media-ecology.blogspot.com /2011/03/google.html